CASE REPORT: OVERCROWDED DI RUANG IGD RUMAH SAKIT RUJUKAN COVID SELAMA MASA PANDEMI COVID-19 - Adi Buyu Prakoso (JURNAL MEDIKA USADA, 2023)
The number of confirmed and suspected cases is still increasing as a result of the Coronavirus Disease (Covid-19). Hospital readiness in dealing with this pandemic is very much needed, especially in terms of human resources. Health workers in hospitals, especially doctors, nurses and ambulance workers, are more likely to be infected than other groups. This study aims to report cases of the Covid-19 referral hospital in Yogyakarta, where a few months after the determination of cases of exposure to health workers in the emergency room which resulted in overcrowding, several actions have been taken by temporarily closing the emergency room and transferring nursing staff to the emergency room. To overcome this, it can be done by accelerating services in the emergency room, increasing the ability of the triage team, procuring alternative units, increasing access and coordination between the community sector and hospitals. Transferring patients from the appropriate ED at the right time as well as creating more inpatient beds and building larger EDs is possible